Exploring Microemulsion Systems for the Incorporation of Glucocorticoids into Bacterial Cellulose: A Novel Approach for Anti-Inflammatory Wound Dressings - Paul Zahel; Vera Bruggink; Juliana Hülsmann; Frank Steiniger; Robert K. Hofstetter; Thorsten Heinzel; Uwe Beekmann; Oliver Werz; Dana Kralisch (MDPI AG, 2024)
The effective pharmacological treatment of inflamed wounds such as pyoderma gangraenosum remains challenging, as the systemic application of suitable drugs such as glucocorticoids is compromised by severe side effects and the inherent difficulties of wounds as drug targets. Furthermore, conventional semi-solid formulations are not suitable for direct application to open wounds. Thus, the treatment of inflamed wounds could considerably benefit from the development of active wound dressings for the topical administration of anti-inflammatory drugs. Although bacterial cellulose appears to be an ideal candidate for this purpose due to its known suitability for advanced wound care and as a drug delivery system, the incorporation of poorly water-soluble compounds into the hydrophilic material still poses a problem. The use of microemulsions could solve that open issue. The present study therefore explores their use as a novel approach to incorporate poorly water-soluble glucocorticoids into bacterial cellulose. Five microemulsion formulations were loaded with hydrocortisone or dexamethasone and characterized in detail, demonstrating their regular microstructure, biocompatibility and shelf-life stability. Bacterial cellulose was successfully loaded with the formulations as confirmed by transmission electron microscopy and surprisingly showed homogenous incorporation, even of w/o type microemulsions. High and controllable drug permeation through Strat-M® membranes was observed, and the anti-inflammatory activity for permeated glucocorticoids was confirmed in vitro. This study presents a novel approach for the development of anti-inflammatory wound dressings using bacterial cellulose in combination with microemulsions.